PENGARUH MODAL KERJA TERHADAP PENJUALAN DAN PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2018-2023 - Parwati, Ni Ketut; Ferayani, Made Dwi (Komunitas Manajemen Kompetitif, 2024)
The purpose of this study was to determine the effect of working capital on sales and profitability. This research uses a quantitative approach. The population in this study were cement sub-sector companies listed on the IDX in 2018-2023. The sampling method in this study used a type of non-probability sampling with purposive sampling technique. The data collection technique in this study used documentation techniques and literature studies. The data analysis technique in this study uses the classical assumption test, simple linear regression analysis test, hypothesis testing (t test) and the coefficient of determination. The results of this study indicate that, 1) partially the working capital variable (X) has an effect on sales (Y1). Where the t value obtained is 6,123 with a significant value (sig) of 0,000 < 0,05 with a percentage contribution of 38,1% while the remaining 61,9% is influenced by other variables not included in this study. 2) partially the working capital variable (X) has an effect on profitability (operating profit) (Y2). Where the t value obtained is 6,183 with a significant value (sig) of 0,000 < 0,05 with a percentage contribution of 38,5% while the remaining 61,5% is influenced by other variables not included in this study.